Volumetric Evaluation of Voids and Gaps of Different Calcium-Silicate Based Materials Used in Furcal Perforations: A Micro-CT Study - Cassia Cestari Toia; Fabricio Batista Teixeira; Carolina Cucco; Marcia Carneiro Valera; Bruno Neves Cavalcanti (MDPI AG, 2022)
This study aimed at evaluating volumetrically gaps and voids of calcium-silicate based materials of different generations and handling properties (BC-Endosequence BC RRM-Fast Set Condensable Putty, MTA-ProRoot MTA, and BIO-Biodentine) in simulated furcal perforations in an ex vivo setup by microcomputed tomography (Micro-CT) analysis. Thirty-six extracted human mandibular molars with sound furcation areas were selected. Standardized perforations were created in the furcation area of the pulp chamber using #4 diamond burs. The specimens were randomly assigned to three groups (BC, MTA and BIO; n = 12). Samples were then scanned (SkyScan 1172; Bruker-microCT, Kontich, Belgium), and three-dimensional (3D) images reconstructed. The relative volume of gaps (VG%) and voids (VV%) present on each material was calculated. Data were analyzed using one-way analysis of variance (ANOVA) and Tukey's HSD test (p < 0.05). Mean VG% for BC, MTA, and BIO groups were, respectively, 0.513%, 1.128%, 1.460%, with BC presenting statistically (p < 0.05) fewer gaps formation than the other groups. Mean VV% were, respectively, 0.018%, 0.037%, and 0.065%. The was no statistical difference regarding VV%. There were no gap-free and void-free samples. BC group had the lowest VG% among the groups with a significant statistical difference (p < 0.05).